2014
DOI: 10.1097/pas.0000000000000304
|View full text |Cite
|
Sign up to set email alerts
|

Activating BRAF V600E Mutation in Aggressive Pediatric Langerhans Cell Histiocytosis

Abstract: Langerhans cell histiocytosis (LCH) is a rare neoplastic disease originating from cells characterized by antigen-presenting Langerhans cell phenotype. The clinical spectrum of LCH is highly variable including localized and disseminated forms mostly occurring in children. Recently, about 60% of LCHs were reported to carry the activating BRAF mutation V600E. In our retrospective study, we evaluated the occurrence and prognostic impact of the V600E mutation in formaldehyde-fixed, paraffin-embedded samples from 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Additionally, small neoplastic foci might be insufficient to detect by PCR. This is similar to the reported false negativity of a PCR reaction caused by low tumor cell quantities in the presence of sporadic tumor cells within massive nonneoplastic tissues 24 . It was also speculated to result from mutations in proteins that share similar epitopes, such as ARAF or CRAF 22 …”
Section: Discussionsupporting
confidence: 71%
“…Additionally, small neoplastic foci might be insufficient to detect by PCR. This is similar to the reported false negativity of a PCR reaction caused by low tumor cell quantities in the presence of sporadic tumor cells within massive nonneoplastic tissues 24 . It was also speculated to result from mutations in proteins that share similar epitopes, such as ARAF or CRAF 22 …”
Section: Discussionsupporting
confidence: 71%
“…Recently, this mutation has been proposed to be associated with the most aggressive forms of LCH. 5,12,31 Our finding is surprising, as all our cases had multisystemic involvement with a fatal outcome. However, it has also been reported that Asian patients with LCH tend to show a lower rate of BRAF V600E mutation with a frequency ranging from 20-24% in different studies.…”
Section: Discussionmentioning
confidence: 62%
“…When present, it denotes an aggressive behavior and treatment refractoriness. [ 54 55 ] Juvenile xanthogranuloma (JXG) and reticulohistiocytomas are other histiocytic disorders commonly affecting skin. The tumor cells express CD68, alpha1 antitrypsin, alpha 1 antichymotrypsin, and factor XIII, but they are negative for LCH markers like CD1a, S-100, and Langerin [Figure 5d – f ].…”
Section: Histiocytic Lesionsmentioning
confidence: 99%